EXPERIMENTAL STUDY ON COMPOSITE RETROFIT METHOD ON FIRE DAMAGED HIGH-STRENGTH CONCRETE BEAM - EMANUEL, NICHOLAS
Bridge structures are designed to withstand uniform loads, concentrated line loads, moving loads, as well as the self-weight and components of the bridge. However, in Indonesia, the potential for fires under bridges is often not considered. These fires can damage the structural integrity and strength due to high temperatures causing cracking, spalling, carbonation, and the deterioration of concrete and reinforcement quality. The impact of such fires is often not accounted for in the design, necessitating repairs (retrofit). Therefore, it is crucial to investigate the behavior and impact of commonly used repair methods. In this study, eight high-strength concrete beams (41.5 MPa) representing bridge girders will be subjected to a constant temperature of 800 °C for 2 hours. The specimens are divided into four groups: BH-1 (unreinforced), BH-2 (epoxy-injected and flexurally reinforced with FRP), BH-3 (concrete cover replaced with mortar and flexurally reinforced with FRP), and BH-4 (concrete cover replaced with mortar, flexurally reinforced with FRP, and shear reinforced with FRP using a U-Wrap scheme). The main objective of this research is to evaluate the behavior of beams exposed to high temperatures and their performance after repair using common methods. Experimental results indicate that high-strength beams initially experiencing flexural failure underwent shear compression failure after exposure to high temperatures. The reinforcement applied was unable to change the mode of shear compression failure due to the inadequate shear capacity. The repair successfully restored almost all of the stiffness and ultimate load, but ductility was not recovered due to the brittle nature of shear compression failure. Repair by replacing the concrete cover with mortar and adding flexural FRP reinforcement fully restored stiffness.